THE SYNTHESIS OF PBZR0.52TI0.48O3 AND PBZR0.58TI0.42O3 CERAMIC POWDER BY USE MOLTEN SALT METHOD AND ITS INTERMEDIATE PRODUCT ANALYSIS - Ahda, Syahfandi; Mardiyanto, Mardiyanto; Taufiq, Agus; Silalahi, Marzuki (Majalah Ilmiah Pengkajian Industri, 2019)
Lead zirconat titanate, Pb(Zr1-x,Tix)O3 is a material with high piezoelectric properties and many studies have been carried out in development, in order to improve the materials quality in various applications. Therefore,one of them is the development of synthesis with the molten salt method in this study. Choice of the molten salt method is simply and and not expensive. The salt ratio of NaCl / KCl at 1: 1 in moles as a solvent medium was carried out in synthesizing Pb(Zr1-x,Tix)O3. Likewise, the salt ratio with reactant/basic material was 1: 1 in weight percentages. An intermediate product is obtained if the dynamics of chemical reactions in the diffusion process occur indirectly or in stages. To identify intermediate products in this synthesis process, the sintering temperature has been varied to 575, 675 and 775 oC for samples A, B and C, respectively. The results of these syntheses have been identified and characterized using x-ray diffraction (XRD) methods. The Highscore program using the Rietveld method to identify the intermediate product content and each crystal structure has been applied in the rifenement process on the XRD intensity profile with a statistical error of less than 6%. Intermediate products have been obtained as follows, PbTiO3, PbZrO3 and Zr0.4Ti0.6O3. Whereas sample C has obtained two phases namely PbZr0.52Ti0.48O3 and PbZr0.58Ti0.42O3 with tetragonal (P4mm) and rhombohedral crystal structures (R3c).